Analisis Perbandingan Sistem Pemungutan Pajak terhadap Kontribusi dan Efektivitas Pajak Daerah yang Potensial di Kabupaten Tanah Bumbu - Monika, Sela; Muzdalifah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine the contribution and effectiveness of taxes collected by the Official Assessment System (PBB-P2) compared to the Self Assessment System (BPHTB, PPJ, Restaurant Tax, and MBLB Tax) on Local Revenue Tanah Bumbu Regency. The method used in this research is quantitative descriptive with contribution and effectiveness analysis techniques using secondary data obtained from the Regional Tax and Retribution Management Agency of Tanah Bumbu Regency. The result of this research is that the tax contribution collected by the Self Assessment System is better than that collected by the Official Assessment System. Even though it is still in the criteria of not contributing, theree are also types of taxes in the shallow standards, namely Restaurant Tax and MBLB Tax. The taxes collected by the Official Assessment System and the Self Assessment System were very effective in 2016-2020. This means that the average realization for the last five years has consistently reached the target.